Penerapan Nilai Budaya Legenda Lau Kawar Sebagai Pembelajaran BIPA - Florentina Sagala; Rika Maharani; Ruth Silvia Sitorus; Safinatul Hasanah Harahap (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
A legendary story that can be used as BIPA teaching material is the Legend of Lau Kawar. This legend comes from North Sumatra and tells the story of the origin of Lake Lau Kawar which is full of meaning and cultural values. The aim of this research is to describe the cultural values ​​of the Legend of Lau Kawar as an application in BIPA learning. This research method is qualitative research using library study data collection techniques, the data source is the story of the Lau Kawar legend originating from Karo. The results of the research show that BIPA students can learn the cultural values ​​contained in the legendary story of Lau Kawar as follows. First, the residents of Kawar village held a thanksgiving party as a form of gratitude to God for the blessings of an abundant harvest. Second, the residents of Kawar village worked together to create a thanksgiving party. Third, you must appreciate and respect. An attitude of respect and respect for parents is the most important thing for us to obey.